Ovalbumin-Induced Allergic Inflammation Diminishes Cross-Linked Collagen Structures in an Experimental Rabbit Model of Corneal Cross-Linking - Zhao, Zhongyang; Liang, Minghui; He, Huan; Wang, Xuemei; Zhu, Chengfang; Li, Lan; Liu, Bin; Zong, Rongrong; Jin, Qifang; Wu, Huping; Li, Wei; Lin, Zhirong (Frontiers in Medicine, 2022)
Background: Allergic conjunctivitis (AC) is a potential risk factor for the progression of keratoconus after corneal collagen crosslinking (CXL) surgery; however, the causal relationship remains inconclusive. Recent evidence indicates that various inflammatory cytokines play a vital role in the development of primary keratoconus, and it is still unclear whether these inflammatory mediators also trigger CXL failure. This study aimed to investigate the effect of AC on rabbit corneas after trans-epithelial CXL (TCXL). Methods: Six untreated rabbits were used as normal controls (NC group). Eighteen rabbits were treated with TCXL and divided into three groups (six in each group) according to additional treatment: no treatment (TCXL group), induction of AC (TCXL+AC group), and induction of AC plus topical application of prednisolone acetate (TCXL+AC+PA group). AC was induced via topical application of ovalbumin after intraperitoneal pre-sensitization with the same agent. The rabbits were evaluated via slit lamp examination, in vivo laser scanning confocal microscopy, anterior segment optical coherence tomography, and corneal biomechanics measurement. Corneal specimens were collected for transmission electron microscopy, collagenase I digestion, and PCR assay for tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-1β, matrix metalloproteinase (MMP)-9, lysyl oxidase (LOX), and tissue inhibitor of metalloproteinase (TIMP)-1 on day (D) 28. Results: On D28, the TNF-α, IL-6, IL-1β, MMP-9, and LOX levels significantly increased, while the TIMP-1 level decreased in TCXL+AC group compared with those in TCXL and TCXL+AC+PA groups. In vivo confocal microscopy revealed that at a depth of 150–210 μm, a trabecular-patterned hyperdense structure surrounded by elongated needle-like processes could be observed in TCXL and TCXL+AC+PA groups, but hardly seen in TCXL+AC group. The demarcation lines were indistinct and blurred in TCXL+AC group. Electron microscopy revealed fewer interlacing fibril lamellae and lower density of collagen fibrils in TCXL+AC group than in the other groups. The stability of corneal biomechanics and resistance to collagenase decreased in TCXL+AC group. Conclusions: The corneal microstructures induced by TCXL and biomechanical stability were diminished in the rabbits with AC but could be maintained by topical anti-inflammatory treatment. Our results support the causal relationship between altered cytokine profiles and the corneal microstructures after primary CXL.